2022
DOI: 10.1001/jama.2022.13382
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Clinical Decision Support With Audit and Feedback on Prevention of Acute Kidney Injury in Patients Undergoing Coronary Angiography

Abstract: ImportanceContrast-associated acute kidney injury (AKI) is a common complication of coronary angiography and percutaneous coronary intervention (PCI) that has been associated with high costs and adverse long-term outcomes.ObjectiveTo determine whether a multifaceted intervention is effective for the prevention of AKI after coronary angiography or PCI.Design, Setting, and ParticipantsA stepped-wedge, cluster randomized clinical trial was conducted in Alberta, Canada, that included all invasive cardiologists at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…In their stepped-wedge, cluster randomised clinical trial, James and colleagues sought to understand the effect of a combined quality improvement intervention, focused on CI-AKI prevention strategies, on rates of AKI among patients undergoing non-emergency coronary angiography in Alberta, Canada 30. The intervention was aimed at cardiologists performing coronary angiography and percutaneous coronary intervention and included education, computerised clinical decision support on contrast volume and hemodynamic-guided intravenous fluid targets and audit and feedback.…”
Section: Effect Of Clinical Decision Support With Audit and Feedback ...mentioning
confidence: 99%
“…In their stepped-wedge, cluster randomised clinical trial, James and colleagues sought to understand the effect of a combined quality improvement intervention, focused on CI-AKI prevention strategies, on rates of AKI among patients undergoing non-emergency coronary angiography in Alberta, Canada 30. The intervention was aimed at cardiologists performing coronary angiography and percutaneous coronary intervention and included education, computerised clinical decision support on contrast volume and hemodynamic-guided intravenous fluid targets and audit and feedback.…”
Section: Effect Of Clinical Decision Support With Audit and Feedback ...mentioning
confidence: 99%
“…The intervention outlined in the study by James et al was consistent with study design principles from the burgeoning field of implementation science . The initial educational session likely promoted clinician awareness and garnered buy-in for the intervention .…”
mentioning
confidence: 92%
“…Case studies of successful clinical decision support interventions can provide valuable information on best practices, including institutional and policy environments that facilitate this type of innovation. In this issue of JAMA , James et al report a pragmatic, cluster randomized clinical trial combining education, clinical decision support–based algorithms, and scheduled audit and feedback to study the effect of this multifaceted intervention on the development of acute kidney injury (AKI) after intravenous contrast administration during cardiac catheterization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Computer-based clinical decision support is one attractive strategy that has been leveraged in prior studies to prompt physicians to stop nephrotoxic medications after AKI has been identified, 3 yet broad implementation of systematic strategies for preventing and managing AKI has shown variable success. [4][5][6] The Nephrotoxic Injury Negated by Just-In-Time Action (NINJA) initiative is one impressive example of a focused clinical decision support intervention that has been rigorously developed, implemented, and evaluated to prevent harm due to drug-associated AKI in children. 7,8 NINJA is a quality improvement initiative that originated at the Cincinnati Children's Hospital Medical Center.…”
mentioning
confidence: 99%